Genetic variability of astaxanthin-producing yeasts: random amplified polymorphic DNA (RAPD) analysis of Phaffia rhodozyma and Xanthopyllomyces dendrorhous - Palágyi, Zsuzsanna (Acta Biologica Szegediensis, 2004)
Astaxanthin (3,3'-dihydroxy-b,b-carotene-4,4'-dione)-accumulating yeasts are of great biotechnological interest. Random amplified polymorphic DNA (RAPD) analysis involving 5 primers and 13 astaxanthin-producing yeast strains was performed. Cluster analysis based on RAPD markers differentiated isolates of Xanthopyllomyces dendrorhous (self-sporulating) and Phaffia rhodozyma (asexual) at an intraspecific level. Strains considered to be derived from the same isolate, but which had had different strain histories, revealed significant differences in their RAPD patterns. The applicability of RAPD analysis for the species-level differentiation of these yeasts is discussed.